PEMBELAJARAN TARI DI TAMAN KANAK-KANAK NEGERI PEMBINA PLANTUNGAN KABUPATEN KENDAL - Hartono, - (Harmonia: Journal of Arts Research and Education, 2009)
Dance is taught to children early, so children will have basic ability consists of appreciation,perception, knowledge, and understanding. Based on the importance of dance for children,researcher is attracted to study the processes of dance learning in TK Negeri PembinaPlantungan regency of Kendal. Research in this TK Negeri Pembina Plantungan regency ofKendal viewed correct because they give dance learning especially with a good planning andprogram. Data collection techniques are observation, interview, and documentation. Analyzingdata is done by using descriptive-qualitative analysis. Techniques of checking relevance datause cross-recheck validity. Based on research result, dance learning in TK Negeri PembinaPlantungan regency of Kendal, studied in possession of equipment of dance learning aspect,implementation of dance learning, kind of given services, and in the moment of giving materialis the dance learning that can be counterfeited by surrounded TK.Kata kunci: TK N Pembina, pembelajaran tari, anak TK